Caesarean section and associated factors in Nigeria: assessing inequalities between rural and urban areas—insights from the Nigeria Demographic and Health Survey 2018 - Adewuyi, Emmanuel; Akosile, W.; Olutuase, V.; Philip, A.A.; Olaleru, R.; Adewuyi, M.I.; Auta, A.; Khanal, V. (2024)
Introduction: When medically indicated, caesarean section (CS) can be a life-saving intervention for mothers and their newborns. This study assesses the prevalence of CS and its associated factors, focussing on inequalities between rural and urban areas in Nigeria. Methods: We disaggregated the Nigeria Demographic and Health Survey 2018 and performed analyses separately for Nigeria’s overall, rural, and urban residences. We summarised data using frequency tabulations and identified factors associated with CS through multivariable logistic regression analysis. Results: CS prevalence was 2.7% in Nigeria (overall), 5.2% in urban and 1.2% in rural areas. The North-West region had the lowest prevalence of 0.7%, 1.5% and 0.4% for the overall, urban and rural areas, respectively. Mothers with higher education demonstrated a greater CS prevalence of 14.0% overall, 15.3% in urban and 9.7% in rural residences. Frequent internet use increased CS prevalence nationally (14.3%) and in urban (15.1%) and rural (10.1%) residences. The southern regions showed higher CS prevalence, with the South-West leading overall (7.0%) and in rural areas (3.3%), and the South-South highest in urban areas (8.5%). Across all residences, rich wealth index, maternal age ≥ 35, lower birth order, and ≥ eight antenatal (ANC) contacts increased the odds of a CS. In rural Nigeria, husbands’ education, spouses’ joint healthcare decisions, birth size, and unplanned pregnancy increased CS odds. In urban Nigeria, multiple births, Christianity, frequent internet use, and ease of getting permission to visit healthcare facilities were associated with higher likelihood of CS. Conclusion: CS utilisation remains low in Nigeria and varies across rural-urban, regional, and socioeconomic divides. Targeted interventions are imperative for uneducated and socioeconomically disadvantaged mothers across all regions, as well as for mothers in urban areas who adhere to Islam, traditional, or ‘other’ religions. Comprehensive intervention measures should prioritise educational opportunities and resources, especially for rural areas, awareness campaigns on the benefits of medically indicated CS, and engagement with community and religious leaders to promote acceptance using culturally and religiously sensitive approaches. Other practical strategies include promoting optimal ANC contacts, expanding internet access and digital literacy, especially for rural women (e.g., through community Wi-Fi programs), improving healthcare infrastructure and accessibility in regions with low CS prevalence, particularly in the North-West, and implementing socioeconomic empowerment programs, especially for women in rural areas.